2000
DOI: 10.1039/b001912g
|View full text |Cite
|
Sign up to set email alerts
|

A study of the effects of acid on the polymerisation of pyrrole, on the oxidative polymerisation of pyrrole and on polypyrrole

Abstract: The polymer products arising from the hydrochloric acid treatment of aqueous pyrrole were shown to have spectroscopic data consistent with alternating pyrrole and pyrrolidine units with varying degrees of ring opening of the pyrrole units. The acid catalysed polymerisation of pyrrole offers a facile route to polymers with amine and carbonyl functional groups, which could be further derivatised. The products were polydisperse spheres; however the use of steric stabilisers induced monodisperse sphere formation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 18 publications
5
42
0
Order By: Relevance
“…A similar pattern is observed in the synthesis in supercritical CO 2 , but, along with the presence of excess oxidant in the reaction zone, there is another negative factor: elevated temperature (75oC), which accelerates both the formation of saturated fragments and other side reactions (e.g., deamination [14] and overoxidation of polypyrrole). Furthermore, the source of pyrrole in the polymerization in supercritical CO 2 , is pyrrole-2-carboxylic acid, which also favors acceleration of the acid-catalyzed side reaction.…”
Section: Chemical Structure Of Pe/ppyr Composite Systemssupporting
confidence: 65%
See 1 more Smart Citation
“…A similar pattern is observed in the synthesis in supercritical CO 2 , but, along with the presence of excess oxidant in the reaction zone, there is another negative factor: elevated temperature (75oC), which accelerates both the formation of saturated fragments and other side reactions (e.g., deamination [14] and overoxidation of polypyrrole). Furthermore, the source of pyrrole in the polymerization in supercritical CO 2 , is pyrrole-2-carboxylic acid, which also favors acceleration of the acid-catalyzed side reaction.…”
Section: Chemical Structure Of Pe/ppyr Composite Systemssupporting
confidence: 65%
“…n , where n = 1, 2] and rise in the solution acidity [14,17]. Thus, because the main process (oxidative polymerization) is usually accompanied by the side reaction, PPyr contains a certain amount of saturated units making lower the electrical conductivity of the polymer.…”
Section: Chemical Structure Of Pe/ppyr Composite Systemsmentioning
confidence: 99%
“…42 The presence of this latter bond seems surprising. Nevertheless, CO bond has already been observed in the literature in the case of chemical polymerization of Py and assigned to the overoxidation of polypyrrole.…”
Section: Resultsmentioning
confidence: 92%
“…For example, Kang et al synthesized PPy using iodine, bromine, and chlorine for simultaneously oxidatizing and polymerizing pyrrole . It has also been shown that pyrrole can be polymerized in the presence of strong acids and the mechanism of polymerization was proposed to involve initially protonation of pyrrole at the C‐3 position . The Ti 3 C 2 T x has a strongly pronounced acidic character and its interaction with pyrrole may result in a protonated molecule, which then reacts with unprotonated pyrrole to form a dimer, that subsequently undergoes further reaction with either protonated or unprotonated pyrrole .…”
mentioning
confidence: 99%